Avaliação de manifestações patológicas em construções históricas no município de Caraúbas-RN - Silva, Anderson Nunes (Universidade Federal Rural do Semi-Árido, 2018)
The constructed material patrimony corresponds to historic buildings that bear the reference and identity of a group of society. Therefore, the preservation and maintenance of historic buildings is important for the transfer of knowledge and the perpetuation of patrimony. Therefore, the study of the pathology of buildings is of paramount importance in order to identify the mechanisms, causes and origins of the pathological manifestations that cause a reduction of the useful life and leave more costly with repair in the buildings. In this way, this work presents a diagnosis and proposal of therapy of the pathological manifestations found in buildings of importance history of Caraúbas-RN. The procedures for carrying out this work were: survey of buildings of historical importance for the city; inspection in these constructions with the aid of checklist of pathological manifestations, sketches or ground plan of the building, photographic records and scalimetres; use of diagnostics matrix and definition of the order of priority in the future actions of intervention applying the Gravity Matrix; Urgency and Tendency (GUT). In Caraúbas-RN, the main buildings of cultural esteem found were: São Sebastião's Mother Church, Popular Culture House, Caraúbas Municipality, Caraúbas Municipal Public Market Delmiro Fernandes de Oliveira, Fazenda Casa Sabe Muito and Casa Grande of Colonel Quincas Saldanha. The studies of the diagnoses of the manifestations were in the House of the farm Knows a lot and House of Popular Culture. The most identified anomalies were cracks, cracks, stains, disintegration, disintegration and debarking. The main causes were infiltration, retraction and expansion of the masonry by water absorption, retraction and expansion by thermal movement, biological agents and their excretions and inefficiency of elements used as wick. As a possible therapy proposal it was suggested the use of techniques such as sealing with epoxy resin or use of cement cream with adequate consistency in the cracks, and for the spots, degradation, peeling and disgracin the removal of the affected parts and preparation of the place to be repainted or applied new coating. Therefore, the identified pathological defects had as initial prioritization of the problems the deterioration of the building timber, cracks in masonry / coating, disintegration, disintegration, peeling and staining.
Monografia
Keywords: Patrimônio; Edificações; Estudo da Patologia; Diagnóstico e Terapia; ENGENHARIAS::ENGENHARIA CIVIL